b - Roy, Ajoy.; Khan, Shamsuzzaman (Dhaka : Bangla Academy, 2012)
Collection of documents on the 1971 Bangladesh freedom movement.
Includes bibliographical references and index.
In Bengali.
Keywords: Bangladesh -- History -- Revolution, 1971- -- Sources